Determining extreme heat vulnerability of Harare Metropolitan City using multispectral remote sensing and socio-economic data. Issue 1 (2nd January 2018) - Mushore, Terence D.; Mutanga, Onisimo; Odindi, John; Dube, Timothy
Abstract: Urbanisation alters surface landscape characteristics through conversion of natural landscapes to impervious surfaces. Such changes alter the thermal properties of urban landscape mosaics, increasing the urban heat island intensity and the population's vulnerability to heat-related stress. This study aimed at deriving detailed area-specific spatial information on the distribution of heat vulnerability in Harare city, Zimbabwe, valuable for informed urban thermal mitigation, planning and decision-making. Using Landsat-8-derived bio-physical surface properties and socio-demographic factors, findings show that vulnerability to heat-related distress was high in over 40 percent of the city, mainly in densely built-up areas with low-income groups. Comparatively, low to moderate heat vulnerability was observed in the high-income northern suburbs with low physical exposure and population density. Results also showed a strong spatial correlation (α = 0.61) between heat vulnerability and observed surface temperatures in the hot season, signifying that land surface temperature is a good indicator of heat vulnerability in the area. Furthermore, the study showed that indices derived from moderate-resolution Landsat 8 data improve thermal risk assessment in areas of close proximity. These findings demonstrate the value of readily available multispectral data-sets in determining areas vulnerable to temperature extremes within a heterogeneous urban landscape. The findings are particularly valuable for designing heat-mitigation strategies as well as identifying highly vulnerable areas during heat waves.